Endothelial cell autoantibodies interact with albuminuria in predicting declining renal function, end-stage renal disease or death in adult type 2 diabetic nephropathy - Zimering, Mark; Zhang, Jane H.; Guarino, Peter; Emanuele, Nicholas; McCullough, Peter; Fried, Linda (Frontiers in Endocrinology, 2014)
Albuminuria is a strong predictor of diabetic nephropathy chronic kidney disease outcomes. Yet therapeutic albuminuria-lowering has not consistently translated into a reduction in clinical events suggesting the involvement of additional pathogenic factors. Our hypothesis is that anti-endothelial cell autoantibodies play a role in development and progression in diabetic nephropathy. We determined anti-endothelial cell antibody (AECA) bioactivity in protein A-elutes of baseline plasma in 305 participants in the VA NEPHRON-D study, a randomized trial of angiotensin receptor blocker or dual angiotensin receptor blocker plus angiotensin converting enzyme inhibitor therapy in type 2 diabetes with proteinuric nephropathy. Thirty-eight percent (117/305) of participants had significantly reduced endothelial cell survival (< 80%) in the IgG fraction of plasma. A VA NEPHRON-D primary endpoint (end stage renal disease, significant reduction in estimated glomerular filtration rate, or death) was experienced by 58 individuals. In adjusted Cox regression analysis, there was a significant interaction effect of baseline anti-endothelial cell mediated cell survival and albuminuria on the hazard rate (HR) for primary composite endpoint (P = 0.017). Participants lacking strongly inhibitory antibodies with albuminuria > 1 g/g creatinine had a significantly increased primary event hazard ratio, 3.41- 95% confidence intervals (CI 1.84-6.33; P < 0.001) compared to those lacking strongly inhibitory antibodies with lower baseline albuminuria (< 1 g/g creatinine). These results suggest that anti-endothelial cell antibodies interact significantly with albuminuria in predicting the composite endpoint of death, end stage renal disease or substantial decline in renal function in older, adult type 2 diabetic nephropathy.